Growth of Candida species on complete dentures: effect of microwave disinfection - Sanita, Paula Volpato [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Microwave disinfection of complete dentures has been recommended to treat denture stomatitis in non-immune compromised patients. Oral candidiasis is a frequent manifestation of HIV infection. The objective of this study is to evaluate the effectiveness of microwave irradiation on the disinfection of complete dentures inoculated with American Type Culture Collection (ATCC) and HIV isolates of five species of Candida. Fifty dentures were made, sterilised and inoculated with the tested microorganisms (C. albicans, C. dubliniensis, C. krusei, C. glabrata and C. tropicalis). After incubation (37 degrees C/48 h), dentures were microwaved (650 W/3 min). Non-irradiated dentures were used as positive controls. Replicate aliquots of suspensions were plated at dilutions 10(-1) to 10(-4) and incubated (37 degrees C/48 h). Colony counts (cfu ml(-1)) were quantified. Dentures were also incubated at 37 degrees C for 7 days. Data were analysed with 2-way anova and Tukey HSD tests (alpha = 0.05). Dentures contaminated with all Candida species showed sterilisation after microwave irradiation. All control dentures showed microbial growth on the plates. The cfu ml(-1) for C. glabrata was higher than those of C. albicans, C. dubliniensis and C. tropicalis whereas the cfu ml(-1) for C. krusei was lower. The cfu ml(-1) for clinical isolates was higher than those of ATCC yeast. Microwave irradiation for 3 min at 650 W resulted in sterilisation of all complete dentures.
Keywords: Denture stomatitis; Candida spp; disinfection; microwaves; complete denture; AIDS